Epidemiological Study Of Coronary Heart Disease (CHD) In Rural Population Of Gurgaon District (Haryana State) - Chadha S.L; Radhakrishnan S; Ramachandran K; Gopinath N (Wolters Kluwer Medknow Publications, 1989)
A community based survey of coronary heart disease (CHD) was carried out on a random rural sample of 3375 adults in the age group 25-64 years in gurgaon district (Haryana) about 50-70 Km. Away from Delhi. CHD was diagnosed either (a) on the basis of clinical history supported by documentary evidence of treatment in a hospital or at home of (b) on ECG evidence in accordance with minnesta code. The overall prevalence rate of CHD on clinical history basis was 5.9 (7.4 in males and 5.1 in females) per 1000 adults in the age group 25-64 years. Increased number of cases were found in the age group 55-64 years both in males and females. The prevalence rate based both on clinical history and ECG criteria is estimated at 27.1/1000. Risk factors for CHD such as hypertension, smoking, family history, obesity and physical activity were studied.